Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi - Jung, Tae Won; Choi, Hyun Ki; Kim, Min-Seop; Yoon, Seong Myeong (Zootaxa, 2017)
Three amphipods of the family Photidae collected from Korean waters are reported here with detailed descriptions and illustrations. The Korean materials of Gammaropsis examined in this study are readily assigned to G. longipropodi by the characteristic shape of gnathopod 2 in males: not slenderly produced posterior margin of the carpus, uniform width of very elongate propodus, and the transverse palm. Among the species of genus Photis, P. fischmanni is only one species bearing stridulation ridges of the basis on gnathopod 2 and coxa 3 simultaneously in females, until now. However, Photis stridulus sp. nov. also show this characteristic but is clearly distinguishable from P. fischmanni by the weak setation of the appendages, smaller eye on the anterior cephalic lobe, and the slender carpus and propodus on gnathopod 1. The genus Podoceropsis is recorded from Korean waters for the first time with the discovery of P. clavapes sp. nov. This new species is characterized by its elongate propodus and dactylus on gnathopod 2 and the shape of the posterior lobe of the basis on pereopod 5 in mature males.